ENVIRONMENTAL REVIEWS AND CASE STUDIES: Streamlining the National Environmental Policy Act Process. (9th February 2015) - Trnka, Joseph; Ellis, Elizabeth
Abstract : The article offers an examination of recent efforts to streamline the NEPA process. Proposed streamlining methods are evaluated to answer whether streamlining initiatives would either improve NEPA or result in a cautionary tale of unintended consequences. Examples are given of commonly encountered sources of delay outside of NEPA that streamlining initiatives cannot address. The article concludes with a discussion of ways to reduce delay in NEPA review. Environmental Practice 16: 302–308 (2014)